ANALISIS DESKRIPTIF STRATEGI PENINGKATAN EFISIENSI LOGISTIK MARITIM - Emha, Faresh; Ariadi, Tiara Sekarwati; Baharudin, Irwan (UNIMAR AMNI Semarang, 2025)
Maritime logistics plays a strategic role in the national and global trade system, especially for an archipelagic country like Indonesia. Tanjung Emas Port, Semarang, is a major logistics distribution hub in Central Java, facing challenges in operational efficiency, logistics system integration, and infrastructure management. This study aims to descriptively analyze strategies for improving maritime logistics efficiency at Tanjung Emas Port in Semarang by 2025. The research method uses a qualitative descriptive approach through observation, documentation studies, and literature reviews. The results show that maritime logistics efficiency is influenced by loading and unloading productivity, port digital integration, infrastructure quality, and coordination between stakeholders. Port digital transformation, container terminal facility improvements, and multimodal system integration are key strategies for improving maritime logistics efficiency. This research is expected to serve as a reference for the development of national logistics policies.